Distribution of planktonic cnidarian assemblages in the southern Gulf of Mexico, during autumn - Martell-Hernandez,Luis F (Sociedad de Biología de Chile, 2014)
BACKGROUND: Despite their ecological, economic and medical relevance, very little information is available on the distribution of planktonic cnidarians, this being particularly true for some regions of the ocean such as the Gulf of Mexico. In fact, the effect of locally important oceanographic features such as the offshore autumnal transport on the distribution of planktonic cnidarians has long been overlooked in this region. Because of this, the present study aimed to analyse the spatial patterns of planktonic cnidarian assemblages in the southern Gulf of Mexico during the autumn of 1998, when particularly intense conditions of convergence, offshore water transportation and productivity were recorded. The assemblages were described in terms of their composition, abundance (volume), diversity, dominance and equitability. Cluster (Bray-Curtis index) and ordination (multidimensional scaling (MDS)) analysis were performed in order to link the observed distribution of species with the environmental parameters. RESULTS: Sixty-eight taxa were recorded, with Koellikerina fasciculata and Muggiaea atlantica representing new records for the region. The holoplanktonic species Diphyes dispar, Abylopsis spp., Liriope tetraphylla, Diphyes bojani, Aglaura hemistoma, Muggiaea kochi, Chelophyes appendiculata and Eudoxoides mitra were dominant with respect to abundance (ml/1000 m³) and frequency of occurrence and defined the differences among the groups of stations. Four groups of sampling stations were identified: (A) the mouth of the Grijalva-Usumacinta system, (B) the Campeche Bank, (C) the area of offshore oil rigs and (D) the continental shelf off Tabasco and associated oceanic waters. The parameters that defined the groups of stations were zooplankton volume, sampling station depth, salinity and dissolved oxygen concentration. CONCLUSIONS: Planktonic cnidarians are useful as indicators of water masses, since the observed zonation was congruent with the surface circulation patterns that are present during the autumn (offshore transportation) and the presence of particular local environmental conditions, including those at the mouth of the Grijalva-Usumacinta system and those associated with the area of oil rigs. We would expect that similar conditions of strong offshore transport would lead to a similar horizontal stratification in the assemblages of planktonic cnidarians in other parts of the world, driven mainly by salinity, oxygen, depth and zooplankton gradients.